Clinical Variability of SYNJ1-Associated Early-Onset Parkinsonism - Lesage, Suzanne; Mangone, Graziella; Tesson, Christelle; Bertrand, Hélène; Benmahdjoub, Mustapha; Kesraoui, Selma; Arezki, Mohamed; Singleton, Andrew; Corvol, Jean-Christophe; Brice, Alexis (Frontiers in Neurology, 2021)
Autosomal recessive early-onset parkinsonism is clinically and genetically heterogeneous. Mutations of three genes, PRKN, PINK1, and DJ-1 cause pure phenotypes usually characterized by levodopa-responsive Parkinson's disease. By contrast, mutations of other genes, including ATP13A2, PLA2G6, FBXO7, DNAJC6, SYNJ1, VPS13C, and PTRHD1, cause rarer, more severe diseases with a poor response to levodopa, generally with additional atypical features. We performed data mining on a gene panel or whole-exome sequencing in 460 index cases with early-onset (≤ 40 years) Parkinson's disease, including 57 with autosomal recessive disease and 403 isolated cases. We identified two isolated cases carrying biallelic mutations of SYNJ1 (double-heterozygous p.D791fs/p.Y232H and homozygous p. Y832C mutations) and two siblings with the recurrent homozygous p.R258Q mutation. All four variants were absent or rare in the Genome Aggregation Database, were predicted to be deleterious on in silico analysis and were found to be highly conserved between species. The patient with both the previously unknown p.D791fs and p.Y232H mutations presented with dystonia-parkinsonism accompanied by a frontal syndrome and oculomotor disturbances at the age of 39. In addition, two siblings from an Algerian consanguineous family carried the homozygous p.R258Q mutation and presented generalized tonic-clonic seizures during childhood, with severe intellectual disability, followed by progressive parkinsonism during their teens. By contrast, the isolated patient with the homozygous p. Y832C mutation, diagnosed at the age of 20, had typical parkinsonism, with no atypical symptoms and slow disease progression. Our findings expand the mutational spectrum and phenotypic profile of SYNJ1-related parkinsonism.